2015
DOI: 10.1136/heartjnl-2015-308569
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial deformation parameters predict outcome in patients with repaired tetralogy of Fallot

Abstract: http://www.clinicaltrials.gov: NCT00266188; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 30 publications
3
84
0
3
Order By: Relevance
“…Our risk score can be used as an initial step to differentiate low-risk from high-risk patients. The high-risk patients could be referred for additional risk assessment (including more costly and invasive investigations such as gadolinium-enhanced CMR imaging, catheterisation and/or programmed ventricular stimulation) to identify those patients who should be referred for implantable cardioverter defibrillator implantation for primary prevention 3 9 10 14 15 19 21 24. In patients without fQRS or other major risk factors, patient counselling can be matched on the excellent prognosis and follow-up may be limited to periodic assessment of residual haemodynamic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Our risk score can be used as an initial step to differentiate low-risk from high-risk patients. The high-risk patients could be referred for additional risk assessment (including more costly and invasive investigations such as gadolinium-enhanced CMR imaging, catheterisation and/or programmed ventricular stimulation) to identify those patients who should be referred for implantable cardioverter defibrillator implantation for primary prevention 3 9 10 14 15 19 21 24. In patients without fQRS or other major risk factors, patient counselling can be matched on the excellent prognosis and follow-up may be limited to periodic assessment of residual haemodynamic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…34 Orwat et al reported a correlation between LV and RV global systolic strain in patients with rTOF; they showed the LV-RV interaction using strain analysis measured by cardiac magnetic resonance (CMR) imaging. 29 Cheung et al also reported that the increase in RVESA correlated with the decrease in LVCS, demonstrating LV-RV interaction in patients with rTOF. 34 As the myocardial damage in RV progresses over time, it expands to include the LV and becomes severe through the LV-RV interaction.…”
Section: Mechanisms Of Decreased LV Deformation In Patients With Tofmentioning
confidence: 98%
“…Orwat et al reported that in patients with rTOF with an average age of 16 years, the strongest prognostic marker was LVCS. 29 Li et al reported that in patients with rTOF and an average age of 5.4 years, LVCS decreases significantly compared with controls, but only decreases significantly in the septal LS, not the lateral LS. 30 These reports indicate that in young patients with rTOF aged up to their teens, LVCS is an essential tool for evaluating myocardial damage, and is a prognostic marker.…”
Section: Rotation and Torsional Behaviormentioning
confidence: 99%
“…Associations of LV GLS, GCS, GRS, and RV GLS with death and nearly missed death were recently prospectively demonstrated in a large cohort of repaired TOF at a median follow-up of 7.4 years. 56 There is also evidence from STE to suggest that quantitative measures of LA function carry prognostic information. 57 From an inception cohort of the MESA study, it was shown that impairment of LA function precedes development of heart failure in the general population.…”
Section: Prognostic Implicationsmentioning
confidence: 99%